Bottomonium spectroscopy in the quark-gluon plasma - Wolschin, Georg (International journal of modern physics. A, Particles and fields, gravitation, cosmology, 2020)
The spectroscopic properties of heavy quarkonia are substantially different in the quark-gluon plasma (QGP) that is created in relativistic heavy-ion collisions as compared to the vacuum situation that can be tested in pppppp collisions at the same center-of-mass energy. In this paper, a series of recent works about the dissociation of the Υ(nS)Υ(nS)Υ(nS) and χb(nP)χb(nP)χb(nP) states in the hot QGP are summarized. Quarkonia dissociation occurs due to (1) screening of the real quark-antiquark potential, (2) collisional damping through the imaginary part of the potential, and (3) gluon-induced dissociation. In addition, reduced feed-down plays a decisive role for the spin-triplet ground state. Transverse-momentum and centrality-dependent data are well reproduced in Pb-Pb collisions at LHC energies. In the asymmetric ppp-Pb system, alterations of the parton density functions in the lead nucleus account for the leading fraction of the modifications in cold nuclear matter (CNM), but the hot-medium effects turn out to be relevant in spite of the small initial spatial extent of the fireball, providing additional evidence for the generation of a quark-gluon droplet.
Gesehen am 19.11.2020